PENGARUH SELF REGULATED LEARNING DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA DI SMK IPIEMS SURABAYA - Santiago, Robert; Trisnawati, Novi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low academic achievement of eleventh-grade students in the Human Resource Management course at SMK IPIEMS Surabaya. The purpose of this study was to determine the effects of Self Regulated Learning and learning motivation on student learning outcomes. The research employed an explanatory quantitative approach with a total sample of 46 students selected through saturation sampling. Data were collected through questionnaires and documentation of students' Mid-Semester Summative scores, then analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS Statistics 25. The results show that Self Regulated Learning has a significant effect on learning outcomes (Sig. 0.000 < 0.05), while learning motivation does not have a significant effect on learning outcomes (Sig. 0.835 > 0.05). Simultaneously, Self Regulated Learning and learning motivation have a significant effect on learning outcomes (Sig. 0.000 < 0.05), with a coefficient of determination of 0.958, indicating that 95.8% of the variation in learning outcomes can be explained by the two variables. Self Regulated Learning is therefore a more dominant factor in influencing students' learning outcomes than learning motivation.